2004
DOI: 10.1080/jmf.16.6.331.337
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes: universal or selective screening?

Abstract: Given the high prevalence of diabetes, the high proportion of patients potentially not identified with a selective screening in this study and the relatively low cost, universal screening for gestational diabetes seems the best way to identify patients and prevent adverse obstetrical and neonatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Yet, some women have been shown to be at elevated risk for this condition (Roberts, 1993). While indeed, any woman may develop gestational diabetes, specific risk factors include obesity, a family history of diabetes and having previously given birth to a very large infant (Alberico et al, 2004).…”
Section: Attribution Of the Origin Of The Illnessmentioning
confidence: 99%
“…Yet, some women have been shown to be at elevated risk for this condition (Roberts, 1993). While indeed, any woman may develop gestational diabetes, specific risk factors include obesity, a family history of diabetes and having previously given birth to a very large infant (Alberico et al, 2004).…”
Section: Attribution Of the Origin Of The Illnessmentioning
confidence: 99%
“…6 Studies have shown that certain components of prenatal care are somewhat beneficial to the mother and her fetus; for example, smoking cessation programs to reduce the incidence of intrauterine growth retardation 12 ; the use of dietary folate, both preconceptionally and in early pregnancy to prevent neural tube defects 13,14 ; and universal screening for gestational diabetes. 15 In response to a 1985 Institute of Medicine report, 16 the Public Health Service convened an expert panel of 19 health care professionals in 1989 to study the scientific basis of prenatal care. 17 This panel examined what was generally known about prenatal care, identified major concepts and assumptions, and critiqued available research.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have linked adequate prenatal care with lowering the incidence of low birth weight 8–10 ; however, according to Alexander and Kotelchuck, “the relationship between prenatal care and adoption of healthy behaviors has received relatively scant investigation.” 11 The American College of Obstetricians and Gynecologists states that women who have early and regular prenatal care are more likely to have healthier infants 6 . Studies have shown that certain components of prenatal care are somewhat beneficial to the mother and her fetus; for example, smoking cessation programs to reduce the incidence of intrauterine growth retardation 12 ; the use of dietary folate, both preconceptionally and in early pregnancy to prevent neural tube defects 13,14 ; and universal screening for gestational diabetes 15 …”
Section: Introductionmentioning
confidence: 99%
“…The rates of pregnancy complications, such as pre-eclampsia (2.8%), gestational diabetes (0.7%), and pregnancy-induced hypertension (2.5%) reported in this population were lower than current norms in the US. [24][25][26] Approximately 15% of women enrolled in the CPP study were below the poverty level, based on US Census Bureau standards for family income from 1960-70, and these mothers had a mean education level of 10.6 6 2.6 years.…”
Section: Resultsmentioning
confidence: 99%